Some Features of Regular Spaces in Supra Fuzzy Topology - Hoque, M. F.; Hossain, M. S.; Ali, D. M. (Journal of Scientific Research, 2012)
We introduce and study supra fuzzy a-regular spaces and we establish some relationships among them in this paper. We also study some other properties of these concepts and obtain their several features. Keywords: Fuzzy regular spaces; Supra fuzzy regular spaces. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i2.8157 J. Sci. Res. 4 (2), 373-382 (2012)